Ia Diastolic Dysfunction: An Echocardiographic Grade. Issue 1 (4th April 2014) - Pandit, Anil; Mookadam, Farouk; Hakim, Fayaz A.; Mulroy, Eoin; Saadiq, Rayya; Doherty, Mairead; Cha, Stephen; Seward, James; Wilansky, Susan
<x xml:space="preserve">Abstract</x> Objective To demonstrate that a distinct group of patients with Grade Ia diastolic dysfunction who do not conform to present ASE/ESE diastolic grading exists. Method and Results Echocardiographic and demographic data of the Grade Ia diastolic dysfunction were extracted and compared with that of Grades I and II in 515 patients. The mean of age of the cohort was 75 ± 9 years and body mass index did not differ significantly between the 3 groups (P = 0.45). Measurements of left atrial volume index (28.58 ± 7 mL/m2 in I, 33 ± 10 mL/m2 in Ia, and 39 ± 12 mL/m2 in II P < 0.001), isovolumic relaxation time (IVRT) (100 ± 17 msec in I, 103 ± 21 msec in Ia, and 79 ± 15 msec in II P < 0.001), deceleration time (248 ± 52 msec in I, 263 ± 58 msec in Ia, and 217 ± 57 msec in II P < 0.001), medial E/e′ (10 ± 3 in I, 18 ± 5.00 in Ia, and 22 ± 8 in II), and lateral E/e′ (8 ± 3 in I, 15 ± 6 in Ia, and 18 ± 9 in II P < 0.001) were significantly different in grade Ia compared with I and II. These findings remained significant even after adjusting for age, gender, diabetes, and smoking. Conclusion Patients with echocardiographic characteristics of relaxation abnormality (E/A ratio of <0.8) and elevated filling pressures (septal E/e′ ≥15, lateral E/e′ ≥12, average E/e′ ≥13) should be graded as a separate Grade Ia group.